2017
DOI: 10.1088/1361-6528/aa72d5
|View full text |Cite
|
Sign up to set email alerts
|

Sublimation-assisted graphene transfer technique based on small polyaromatic hydrocarbons

Abstract: Advances in the chemical vapor deposition (CVD) growth of graphene have made this material a very attractive candidate for a number of applications including transparent conductors, electronics, optoeletronics, biomedical devices and energy storage. The CVD method requires transfer of graphene on a desired substrate and this is most commonly accomplished with polymers. The removal of polymer carriers is achieved with organic solvents or thermal treatment which makes this approach inappropriate for application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…To pick up long CNTs and release them on arbitrary substrates with minimum contamination, we use thin and large-area organic crystals that do not require wet processes or high-temperature treatments. Anthracene, which consists of three benzene rings, meets such requirements 22 , 23 . We expect the similarity of molecular structure between anthracene and CNTs to lead to strong π – π interactions 24 , possibly improving the efficiency of picking up CNTs from the growth substrates.…”
Section: Resultsmentioning
confidence: 99%
“…To pick up long CNTs and release them on arbitrary substrates with minimum contamination, we use thin and large-area organic crystals that do not require wet processes or high-temperature treatments. Anthracene, which consists of three benzene rings, meets such requirements 22 , 23 . We expect the similarity of molecular structure between anthracene and CNTs to lead to strong π – π interactions 24 , possibly improving the efficiency of picking up CNTs from the growth substrates.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the role of different support layers showed that low-molecular-weight polymers-based support material are preferable than high-molecular weight polymer support layers for clean and contamination-free transfer; e.g., poly(bisphenol A carbonate) is superior to PMMA [36]. Similarly, another group proposed the use of naphthalene as a small-molecular support layer [37], where naphthalene showed [16] Copper foil Ferric chloride solution 1 mol•L −1 [39] Copper foil Ferric chloride solution 2 mol•L −1 [21] Copper foil H2O2:HCl…”
Section: Wet Transfermentioning
confidence: 99%
“…However, the presence of D peaks in the Raman spectra of transferred graphene indicates that the film was damaged during transfer, which might be related to its relatively low mechanical strength. Similarly, polycyclic aromatic hydrocarbons such as naphthalene and pentacene also allow clean transfer as sublimable supporting layers . The weak interaction of pentacene with graphene is crucial as it would not change the band structure and Fermi level of graphene with negligible charge transfer doping .…”
Section: Etching Transfermentioning
confidence: 99%